Quantitative measurement of charge accumulation along a quasi-one-dimensional W5O14 nanowire during electron field emission. Issue 19 (12th March 2020) - Zheng, Fengshan; Pozzi, Giulio; Migunov, Vadim; Pirker, Luka; Remškar, Maja; Beleggia, Marco; Dunin-Borkowski, Rafal E.
Abstract : Electric field map and equipotential contour lines of a quasi-one-dimensional W5 O14 nanowire under an electrical bias of 150 V. Experimental cumulative charge profiles along the length of the nanowire are consistent with theoretical simulations. Abstract : We use an electron holographic method to determine the charge distribution along a quasi-one-dimensional W5 O14 nanowire during in situ field emission in a transmission electron microscope. The results show that the continuous charge distribution along the nanowire is not linear, but that there is an additional accumulation of charge at its apex. An analytical expression for this additional contribution to the charge distribution is proposed and its effect on the field enhancement factor and emission current is discussed.